THE PREPARATION OF STUDENTS FOR THE C.P.A. EXAMINATION. - Rosenkampff, A. H. (The Accounting Review, 1927)
The article presents information related to students preparing for the Certified Professional Accountants examination in the U.S. It has been viewed that the ideal accounting problem should be free from vague, obscure, and ambiguous statement; it should not be too lengthy; and it should permit of solution within the allotted time. Problems prepared by university instructors usually meet these requirements and are, therefore, excellent teaching material for the preparation of students for the accounting profession. But, because of their very virtues such problems are often not suitable as preparatory material for the professional examination; for, on such examinations, the candidate is usually confronted with problems which contain vague and contradictory statements, or mathematical errors, or are so lengthy as to be impossible of solution within the specified time. In a course In accounting problems planned to meet the needs of students, equal emphasis should be placed upon the application of accounting principles as applied to various businesses and upon the art of solving problems. It is not the function of a university to prepare its students for examinations into such professions as law, accounting, or medicine. The aim of the collegiate school of business is usually to prepare its students for business or for some special field of business.